The recognition scene in Euripides’ Iphigenia in Tauris - Βούλγαρης Γεώργιος (Ariadne, 2020)
IN Iphigenia in Tauris, the recognition scene between Iphigenia and Orestes is structured in two parts, is found at the heart of the play, and covers approximately 100 verses (vv. 725–826). It is skillfully prepared by the poet due to both the conception of the letter and the exchange of vows in the first part, while in the second part, both the tokens and the memories of the family’s past play a decisive role. The simultaneous inclusion of recognition and reversal in the plot, has earned the praise of criticism by Aristotle himself, who repeatedly turns to Iphigenia in Tauris to exemplify excellence in plotting and the use of recognition (Poetics 11.1452b3–8, 16.1455a16–19, 17.1455b3–15).